Strategic asset allocation and the risk of the stock market in the long run - David Rey; Heinz Zimmermann (Universität Basel, Wirtschaftswissenschaftliches Zentrum (WWZ), 2005)
Current discussions about public and private pension plans often state that the stock market is less risky in the long run than in the short run. Pension plans with their rather long planning horizon are therefore asked to increase the allocation to the stock market. Such statements, however, usually lack a consistent clarification of the underlying reasons for the asserted positive horizon effect. Therefore, it is important for pension plans (and individual long-term investors alike) to be precise about any rational reasons to allocate a higher fraction of their wealth to the risky stock market. One reason that has become prominent among financial economists only recently, is the mounting empirical evidence of stock market predictability. However, our empirical analysis demonstrates that return predictability and persistent movements in expected returns should not be interpreted as a reliable driving force for a positive horizon effect and the corresponding market timing strategies, least of all when estimation risk is taken into account. Although there is some (weak) evidence of stock market predictability, neither the Swiss nor the U.S. stock market seem to be less risky in the long run than in the short run. Motivated by return predictability, long-term investors should not hold more stocks and should not time the market more aggressively than myopic short-term investors ...
Keywords: 330; Portfolio-Management; Anlageverhalten; Aktienmarkt; Prognose; Volatilität; Schätzung; Schweiz; USA; Heteroskedastizität